Clustering of Unhealthy Lifestyle and the Risk of Adverse Events in Patients With Atrial Fibrillation - Lee, So-Ryoung; Choi, Eue-Keun; Park, Sang-Hyeon; Lee, Seung-Woo; Han, Kyung-Do; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2022)
Background Little is known regarding the risk of clinical outcomes depending on the clustering of lifestyle behaviors after atrial fibrillation (AF) diagnosis. This study evaluated the association between a cluster of healthy lifestyle behaviors and the risk of adverse outcomes in patients with AF. Methods Using the Korean National Insurance Service database, patients who were newly diagnosed with AF between 2009 and 2016 were included. A healthy lifestyle behavior score (HLS) was calculated by assigning 1 point each for non-current smoking, for non-drinking, and for performing regular exercise from the self-reported questionnaire in health examinations. The primary outcome was defined as major adverse cardiovascular event (MACE), including ischemic stroke, myocardial infarction, and hospitalization for heart failure. Results A total of 208,662 patients were included; 7.1% in HLS 0, 22.7% in HLS 1, 58.6% in HLS 2, and 11.6% in HLS 3 groups. Patients with HLS 1, 2, and 3 were associated with a lower risk of MACE than those with HLS 0 (adjusted hazard ratio [95% confidence interval (CI)]: 0.788 [0.762–0.855], 0.654 [0.604–0.708], and 0.579 [0.527–0.636], respectively). After propensity score weighting, consistent results were observed. The risk reduction of healthy lifestyle combinations was consistently observed in various subgroups, regardless of the CHA2DS2-VASc score and oral anticoagulant use. Conclusion Increased number of healthy lifestyle behaviors was significantly associated with lower MACE risk in patients with new-onset AF. These findings support the promotion of a healthy lifestyle to reduce the risk of adverse events in patients with AF.